Communication, partnership and sexual functioning of couples treated for infertility - Czyżkowska, Anna; Jóźwik, Milena (Studia Psychologica: Theoria et praxis, 2013)
The goal of this study was to investigate how infertility changes couples’ relations, communication and sexual functioning. In the research participated 50 women during the treatment of infertility and 50 healthy women in the control group. The study conhrmed our hypothesis. Couples during the treatment of infertility have more problems in their relationship (in comparison to couples without infertility problem) in following aspects: communication, task accomplishment and role performance, affective expression, affective involvement, values and norms. Communication in both groups (study group as well as control group) correlates with sexual satisfaction, the correlation between couples’ relations and sexual satisfaction are higher in healthy women group than in infertile women group.